2018
DOI: 10.1002/app.46341
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation and characterization of soluble aramid

Abstract: It remains a problem to prepare cost-effective aramid with good solubility via a simple method since the commercialization of aromatic polyamides such as Kevlar and Nomex by DuPont in 1960s. Herein, we report the facile preparation and properties of an aromatic polyamide copolymerized by 2,6-naphthalene dichloride (26N-COCl), 4,4 0 -oxydianiline, and m-phenylenediamine. The synthetic route is very facile and cost-effective. The modified aramids possess excellent comprehensive properties. The polymers are solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The solubility of the polymer depends on the morphology/packing pattern/rigidity of the polymer backbone. The solubility is closely related to the structure of the polymer chain; the higher the rigidity and regularity, the poorer the solubility for polyamide 8 . All these polyamides showed good solubility in N‐methyl‐2‐pyrrolidone, N, N‐dimethylacetamide, N, N‐dimethylformamide, dimethyl sulfoxide, m‐cresol, and pyridine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The solubility of the polymer depends on the morphology/packing pattern/rigidity of the polymer backbone. The solubility is closely related to the structure of the polymer chain; the higher the rigidity and regularity, the poorer the solubility for polyamide 8 . All these polyamides showed good solubility in N‐methyl‐2‐pyrrolidone, N, N‐dimethylacetamide, N, N‐dimethylformamide, dimethyl sulfoxide, m‐cresol, and pyridine.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility is closely related to the structure of the polymer chain; the higher the rigidity and regularity, the poorer the solubility for polyamide. 8 All these polyamides showed good solubility in N-methyl-2-pyrrolidone, N, N-dimethylacetamide, N, N-dimethylformamide, dimethyl sulfoxide, m-cresol, and pyridine. Good solubility of these polyamides may be due to the incorporation of the preformed aliphatic C 8 moiety and methylene linkages in the polyamide backbone; which increased the chain flexibility, reduced the chainchain interactions, and prevented the close chain packing.…”
Section: Polyamide Characterizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Xu et al reported [111] the facile preparation of aromatic PAs by copolymerizing 2,6-naphthalene dichloride (26 N-COCl), 4,4 0 -oxydianiline, and m-phenylenediamine through acylation, chlorination, and polycondensation (Scheme 30,P30).Thesepolymers wereeasilyprocessed into films, fibers, and tubes and exhibited high strength. The films were transparent and reported 80% transmittance at 500 nm and displayed high fluorescence.…”
Section: Aromatic Pas Covering Fluorescence Propertymentioning
confidence: 99%